2016
DOI: 10.1063/1.4961253
|View full text |Cite
|
Sign up to set email alerts
|

Persistent nonequilibrium dynamics of the thermal energies in the spin and phonon systems of an antiferromagnet

Abstract: We present a temperature and fluence dependent Ultrafast X-Ray Diffraction study of a laser-heated antiferromagnetic dysprosium thin film. The loss of antiferromagnetic order is evidenced by a pronounced lattice contraction. We devise a method to determine the energy flow between the phonon and spin system from calibrated Bragg peak positions in thermal equilibrium. Reestablishing the magnetic order is much slower than the cooling of the lattice, especially around the Néel temperature. Despite the pronounced m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
38
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 36 publications
1
38
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The complexity of this interplay can leads to a variety of technologically useful behaviors. These effects include anomalous thermal expansion, 1,10,11 optical switching of magnetization, [11][12][13][14][15][16][17] and superconductivity. 18 Understanding the details of this electron-spinlattice interplay remains one of the most challenging scientific problems in condensed matter physics.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] The complexity of this interplay can leads to a variety of technologically useful behaviors. These effects include anomalous thermal expansion, 1,10,11 optical switching of magnetization, [11][12][13][14][15][16][17] and superconductivity. 18 Understanding the details of this electron-spinlattice interplay remains one of the most challenging scientific problems in condensed matter physics.…”
mentioning
confidence: 99%
“…Since the advent of femtosecond pulsed X-ray sources, lattice dynamics have been investigated on ultrafast time scales in a variety of different scientific contexts. [12][13][14][15] A first study of lattice dynamics accompanying ultrafast demagnetization was recently realized by Henighan et al 16 on a thin Fe film grown epitaxially on MgO. These authors observed THz frequency oscillations of the scat-tering intensities, which they attribute to the excitation of coherent longitudinal acoustic phonons building up the strain wave generated by the infrared (IR) excitation pulse.…”
Section: A Introductionmentioning
confidence: 99%
“…The exact temporal behavior of the measured average strain depends on the spatial form of the wave packet [12]. The strain beyond 50 ps arises from heating, which is proportional to the absorbed energy [1, 46,47]. Within our measurement window of 3 ns the thermal expansion shows almost no relaxation because of the slow heat transport out of Bi:YIG, as expected from the low thermal conductivity of garnet [48,49].…”
mentioning
confidence: 99%